Determinan Keputusan Investasi; Studi pada Generasi Sandwich - Kamil, Muchammad Ichsan; Ahmad, Gatot Nazir; Widyastuti, Umi (Program Studi Administrasi Niaga STIA Said Perintah, 2024)
The number of the sandwich generation in Indonesia increased by 33.82% in 2021 compared to 2020. The latest figures also show the looming burden on Millennials to care for their parents. The sandwich generation continues to grow until financial responsibility is no longer limited to parents and biological children, but also to generations above and below who are still family. This is the background to this research which aims to analyze and determine the factors that influence investment decisions among the sandwich generation in Jakarta with an age range of 20 to 31 years. This research uses primary data and data collection methods using questionnaires distributed online. Questionnaire data was collected using Google Form by getting 200 respondents. Data analysis was carried out using the PLS Structural Equation Model (SEM). The findings of this research show that there is a positive and significant influence of financial literacy on investment decisions. Meanwhile, financial literacy on fear of missing out shows an negative affect and significant. Meanwhile, fear of missing out on investment decisions does not have a significant affect.